(untitled) (Faculty of Education Scientific Journal, 2024)
Because of their expanding importance in evaluating surface properties, optical non-destructive technologies for 3D surface metrology have gained importance in research and engineering in recent years. In this study, optical 3D Infinite Focus measurement (IFM) system based on the technology of focus-variation was used for qualitative and quantitative evaluation of alloy Tin (Sn). The capabilities of the system on a series of applications ranging from surface roughness, waviness, bearing ratio, determining of depth and diameter of Sn-0.7Cu solder was demonstrated. Samples used in this study were subject zato micro-hardness tests conduct on a soft material (alloyed Sn) using micro hardness indeed. Sample differences in surface morphology were caused by variations in the load and application that the samples were subjected to during the indentation test. Plotting the soft material’s surface roughness, waviness, and bearing ratio required the use of indentation testing under load, as determined by the micro hardness tool (Sn-0.7Cu). Results from two measurements were used to determine the diameter, depth, surface roughness, waviness and bearing ratio of the alloyed Sn (Sn-0.7Cu) using waviness, roughness and bearing ratio analysis. In order to construct their 3D profile and analyze their surface roughness and waviness of the dented soft material, samples were further examined based on their surface parameter. Results also showed that the unreformed materials processed elastic properties when subjected to some amount of force under the influence of load.